Fireflies. - Cong, Chong. (2012)
Fireflies is a 3 minutes animated short film about an ambitious, under-achieving firelfy uncovers the secret to shining brighter than any other fly - at a price. In this report, the crafting process of the film will be discussed, including difficulties encountered, problem solving, breakthroughs and personal development. The paper will be presented from the point of view of the 2D/3D artist, whose key involvement includes designing, painting and animating.